La exposición al aluminio y su relación con el ambiente y la salud - Torrellas Hidalgo, Rosabel (Tecnogestión: Una mirada al ambiente, 2012)
Aluminum is the third most abundant element in Earth’s crust. Although its toxicity has been demonstrated, geochemical control maintains its bioavailability in harmless parameters. However, natural changes and anthropogenic interventions contribute to its release into the environment which causes an increment of sicknesses in the population and harmful accumulations in environment. The most important sources of nonoccupational exposure to aluminum are food, water, certain medicines and cosmetics, packages and utensils used for foods preparation. This paper is a reflection about different aspects related to exposure of aluminum and its relationship with the environment and health.